2010
DOI: 10.1074/jbc.m110.143800
|View full text |Cite
|
Sign up to set email alerts
|

Pathways Regulating Cytosolic Phospholipase A2 Activation and Eicosanoid Production in Macrophages by Candida albicans

Abstract: Resident tissue macrophages are activated by the fungal pathogen Candida albicans to release eicosanoids, which are important modulators of inflammation and immune responses. Our objective was to identify the macrophage receptors engaged by C. albicans that mediate activation of group IVA cytosolic phospholipase A2 (cPLA2α), a regulatory enzyme that releases arachidonic acid (AA) for production of prostaglandins and leukotrienes. A comparison of peritoneal macrophages from wild type and knock-out mice demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 66 publications
5
51
0
2
Order By: Relevance
“…For example, nonsteroidal anti-inflammatory drugs (NSAIDs), such as indomethacin or ibuprofen, target mainly the COX enzymes, thus prostaglandin biosynthesis, to alleviate inflammation [13]. Interestingly, the recognition of the C. albicans cell wall β-glucan by dectin-1 on the surface of macrophages enhances macrophage cytosolic phospholipase A2 activity and COX expression, thus promoting prostaglandin biosynthesis in the host [4,5]. Prostaglandin E 2 (PGE 2 ) is known to inhibit the Th1 response and promote Th2 immune responses [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, nonsteroidal anti-inflammatory drugs (NSAIDs), such as indomethacin or ibuprofen, target mainly the COX enzymes, thus prostaglandin biosynthesis, to alleviate inflammation [13]. Interestingly, the recognition of the C. albicans cell wall β-glucan by dectin-1 on the surface of macrophages enhances macrophage cytosolic phospholipase A2 activity and COX expression, thus promoting prostaglandin biosynthesis in the host [4,5]. Prostaglandin E 2 (PGE 2 ) is known to inhibit the Th1 response and promote Th2 immune responses [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Together, these observations show that VEGF-induced cPLA 2 phosphorylation and AA release require activation of Src-PLD1-PKC␥ signaling. Previous studies had demonstrated that MAPKs play a role in agonist-induced cPLA 2 activation (38,39). Therefore, to find whether MAPKs play a role in VEGFinduced cPLA 2 activation, we also studied the role of ERK1/2, JNK1, and p38MAPK.…”
Section: Vegf-induced Hrmvec Dna Synthesis Migration Andmentioning
confidence: 99%
“…3C). Various MAPKs were previously reported to take part in cPLA 2 ␣ phosphorylation (57)(58)(59). Therefore, we analyzed the phosphorylation patterns of ERK1/2, p38, JNK, and PI3K-Akt kinases after HA (100 g/ml) treatment over time.…”
Section: Low Molecular Weight Hyaluronic Acid (Lmw Ha)mentioning
confidence: 99%